Facebook Is a Useful Recruitment Strategy for a Randomized Clinical Trial of a Lifestyle Approach to Reverse Metabolic Syndrome. (29th May 2020) - Lohse, Barbara; Faulring, Kathryn; Cook, Claire
Abstract: Objectives: Design and evaluate a Facebook (FB) campaign to recruit a select sample with metabolic syndrome (MetS) to participate in a telephone screening for inclusion in a randomized controlled trial of the efficacy of a lifestyle medicine intervention to reverse MetS. Methods: Inclusion and exclusion criteria for participation in the Enhanced Lifestyles for Metabolic Syndrome (ELM) study informed development of a FB ad, utilizing FB guidelines. After clicking a FB ad, co-morbidity and contact information to schedule a screening call were captured via survey using a Qualtrics platform. Phone screen eligibility was defined as having no listed co-morbidities. Providing contact information in addition was deemed to be complete and phone screen-ready. Phone screen eligibility and readiness frequencies were compared to FB campaign performance data on reach, link clicks, demographics and costing using the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) system. Participation was not incentivized. Results: The 14-day FB campaign, driven by 11 phrases pertinent to MetS, had a potential reach of 690, 000 with ad impressions on 33, 243 unique FB accounts resulting in 1160 ad clicks. Ad impressions appeared mostly in female accounts; 90% of ad clickers were female from 18 to 65y or higher; the majority were >45y. Costs ranged from .47 to .83/click (averaged 0.61). Total campaign costs were 708.57. Of the 1160 ad clicks, 422 moved past survey page 1, 114 were eligible for phone screening and 85 were phone screen-ready. Of the 85 that provided contact details, 51 completed the phone screen and 21 were deemed eligible for the ELM baseline assessment. CHERRIES response rates were: View 3.5%; Survey participation 36.4%; Phone screen eligible 27% and Completion 74.6%. Of those who clicked on the ad, 7.3% were Phone screen-ready and 20.1% starting the survey were Phone screen-ready. Costs were 6.216 to recruit a phone screen eligible person; 8.336/phone screen-ready person; 13.894/phone screen completion and 33.741/ELM baseline screen eligible subject. Personnel time was <4 h for the FB campaign. Conclusions: FB was a cost-effective strategy, requiring minimal personnel investment, to recruit subjects to a MetS clinical trial with demanding inclusion/exclusion criteria. Funding Sources: William G. McGowan Charitable Fund, Wegmans School of Health & Nutrition, RIT.